Free-Living User Perspectives on Musculoskeletal Pain and Patient-Reported Mobility With Passive and Powered Prosthetic Ankle-Foot Components: A Pragmatic, Exploratory Cross-Sectional Study - Kannenberg, Andreas; Morris, Arri R.; Hibler, Karl D. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Studies with a powered prosthetic ankle-foot (PwrAF) found a reduction in sound knee loading compared to passive feet. Therefore, the aim of the present study was to determine whether anecdotal reports on reduced musculoskeletal pain and improved patient-reported mobility were isolated occurrences or reflect a common experience in PwrAF users. Methods: 250 individuals with transtibial amputation (TTA) who had been fitted a PwrAF in the past were invited to an online survey on average sound knee, amputated side knee, and low-back pain assessed with numerical pain rating scales (NPRS), the PROMIS Pain Interference scale, and the PLUS-M for patient-reported mobility. Subjects rated their current foot and recalled the ratings for their previous foot. Recalled scores were adjusted for recall bias by clinically meaningful amounts following published recommendations. Statistical comparisons were performed using Wilcoxon´s signed rank test. Results: Forty-six subjects, all male, with unilateral TTA provided data suitable for analysis. Eighteen individuals (39%) were current PwrAF users, whereas 28 subjects (61%) had reverted to a passive foot. After adjustment for recall bias, current PwrAF users reported significantly less sound knee pain than they recalled for use of a passive foot (-0.5 NPRS, p=0.036). Current PwrAF users who recalled sound knee pain ≥4 NPRS with a passive foot reported significant and clinically meaningful improvements in sound knee pain (-2.5 NPRS, p=0.038) and amputated side knee pain (-3 NPRS, p=0.042). Current PwrAF users also reported significant and clinically meaningful improvements in patient-reported mobility (+4.6 points PLUS-M, p=0.016). Individuals who had abandoned the PwrAF did not recall any differences between the feet. Discussion: Current PwrAF users reported significant and clinically meaningful improvements in patient-reported prosthetic mobility as well as sound knee and amputated side knee pain compared to recalled mobility and pain with passive feet used previously. However, a substantial proportion of individuals who had been fitted such a foot in the past did not recall improvements and had reverted to passive feet. The identification of individuals with unilateral TTA who are likely to benefit from a PwrAF remains a clinical challenge and requires further research.